Antibiotic prophylaxis for ventilator-associated pneumonia in pediatric patients with moderate to severe traumatic brain injury in a hospital in Lima, Peru - Chira Alarcon, Patricia Fiorela (2021)
Introduction: This study evaluates the use of antibiotic prophylaxis for prevention and development of ventilator associated pneumonia (VAP) in pediatric patients with moderate to severe traumatic brain injury (TBI) in order to promote best practices and use the appropriate resources. Methods: A retrospective cohort study of all pediatric patients, between 1 and 18 years, who were admitted and had moderate or severe TBI diagnosis at the Pediatric Emergency Hospital, Lima-Peru. Results: One hundred and forty-five patients with diagnosis of traumatic brain injury (TBI), who received mechanical ventilation for at least 48 hours, were evaluated. We obtained an incidence density of 44.60/1000 ventilator days. No relationship was found between antibiotic prophylaxis and the development of VAP. Likewise, it was found that performing oral hygiene with chlorhexidine reduces the risk of developing VAP by 45% (p = 0.03, CI 0.33-0.95).In addition, the presence of purulent secretions (IC 2.23-11.45), solid (, IC 1.67-11.34) or dense ( IC 2.91-16.75) has a 3, 5 and 6 times higher risk of ventilator-associated pneumonia, respectively. Conclusions: Antibiotic prophylaxis did not show to have a positive effect on the prevention of ventilator associated pneumonia; However, other measures such as oral hygiene with chlorhexidine were associated with reducing the risk of developing VAP. The proportion of patients who received antibiotic prophylaxis was 81 (55.6%) and the incidence density of VAP found in the study is within the standards found in the available literature. Furthermore, the type of discharge was identified as a predictor of increased risk of ventilator-associated pneumonia. Even more studies focused on this population are required.